Genetic and Environmental Risk for Major Depression in African-American and European-American Women. (August 2014) - Duncan, Alexis E.; Munn-Chernoff, Melissa A.; Hudson, Darrell L.; Eschenbacher, Michaela A.; Agrawal, Arpana; Grant, Julia D.; Nelson, Elliot C.; Waldron, Mary; Glowinski, Anne L.; Sartor, Carolyn E.; Bucholz, Kathleen K.; Madden, Pamela A. F.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> It is unknown whether there are racial differences in the heritability of major depressive disorder (MDD) because most psychiatric genetic studies have been conducted in samples comprised largely of white non-Hispanics. To examine potential differences between African-American (AA) and European-American (EA) young adult women in (1) Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) MDD prevalence, symptomatology, and risk factors, and (2) genetic and/or environmental liability to MDD, we analyzed data from a large population-representative sample of twins ascertained from birth records (n = 550 AA and n = 3226 EA female twins) aged 18–28 years at the time of MDD assessment by semi-structured psychiatric interview. AA women were more likely to have MDD risk factors; however, there were no significant differences in lifetime MDD prevalence between AA and EA women after adjusting for covariates (odds ratio = 0.88, 95% confidence interval [CI]: 0.67–1.15). Most MDD risk factors identified among AA women were also associated with MDD at similar magnitudes among EA women. Although the MDD heritability point estimate was higher among AA women than EA women in a model with paths estimated separately by race (56%, 95% CI: 29–78% vs. 41%, 95% CI: 29–52%), the best fitting model was one in which additive genetic and non-shared environmental paths for AA and EA women were constrained to be equal (A = 43%, 33–53% and E = 57%, 47–67%). In spite of a marked elevation in the prevalence of environmental risk exposures related to MDD among AA women, there were no significant differences in lifetime prevalence or heritability of MDD between AA and EA young women.